The role of genetics in understanding and improving heat tolerance in tropical African livestock - Habimana, V.; Mrode, Raphael A.; Chenyambuga, S.W.; Ekine-Dzivenu, Chinyere C.; Houaga, I. (CAB International, 2025)
Heat stress (HS) causes a decline in the productivity of livestock through reduced dry matter intake, decreased reproduction rate and adverse effects on the physiological state (e.g., respiration rate, rectal temperature, heart rates, pulse rates, panting score, sweating rates, and drooling score). Indigenous breeds have higher tolerance to HS than their exotic counterparts. However, indigenous breeds have low productivity. Therefore, genetically improving the heat tolerance of high-producing livestock breeds in Africa can enhance animal welfare and reduce production losses during HS conditions. Identifying and measuring appropriate phenotypic indicators of heat tolerance and understanding the genetic basis are very important steps for breeding heat-tolerant animals that are highly adaptable to the climatic conditions in Africa. This case study highlights recent advances on heat tolerance in livestock reared in tropical countries with a focus on Africa, the challenges faced by African countries in estimating the genetic value of heat-tolerant livestock and indicate the future directions for heat tolerance studies in Africa. Moreover, the case study reports genes that have been shown to influence heat tolerance in livestock and discusses the possibility of using them in genomic selection programs.